Calsequestrins New Calcium Store Markers of Adult Zebrafish Cerebellum and Optic Tectum - Furlan, Sandra; Campione, Marina; Murgia, Marta; Mosole, Simone; Argenton, Francesco; Volpe, Pompeo; Nori, Alessandra (Frontiers in Neuroanatomy, 2020)
ABSTRACT Calcium stores in neurons are heterogeneous in compartmentalization and molecular composition. Danio rerio (zebrafish) is an animal model with simply folded cerebellum similar in cellular organization to mammals. Aim of the study was to identify new endoplasmic reticulum calcium store markers in zebrafish adult brain with emphasis on cerebellum and optic tectum. By quantitative Polymerase Chain Reaction we found three RNA transcripts coding for the intra endoplasmic reticulum calcium binding protein calsequestrin: casq1a, casq1b and casq2. In brain homogenates, two isoforms were detected by mass spectrometry and western blotting. Fractionation experiments of whole brain revealed that Casq1a and Casq2 were enriched in a heavy fraction containing endoplasmic reticulum microsomes and synaptic membranes. By in situ hybridization we found heterogeneous expression of casq1a and casq2 mRNA compatible with cellular localization of calsequestrins investigated by immunofluorescence. Casq1 was expressed in neurogenic differentiation 1 expressing granule cells of cerebellum and periventricular zone of optic tectum, Casq2 was concentrated in parvalbumin expressing Purkinje cells. At subcellular level, Casq1 was restricted to granular cell bodies and Casq2 was localized in cell bodies, dendrites and axons. Data are discussed in relation to the differential cellular and subcellular distribution of other cerebellum calcium store markers and are evaluated with respect to the putative relevance of calsequestrins in neuron-specific functional activity.